An Atypical Presentation of Liver Enzyme Elevation Resulting from Bosentan Use - Kimberley Mulchey; Zoheir Bshouty (Canadian Respiratory Journal)
Hepatocellular enzyme elevation is a known side effect of both bosentan and atorvastatin. However, a rise in liver enzyme level not characteristic of either agent individually may represent a reaction to their combination or an atypical reaction to bosentan alone.